Problem-Based Electronic Module on Thaharah Material for Madrasah Tsanawiyah Students - Nihlatul Azizah; Asrowi; Herry Widyastono (Universitas Pendidikan Ganesha, 2024)
Currently, the world is very easily connected with digital devices, including Islamic learning which must follow the development trends of information and communication technology. Therefore, this research aims to develop a digital learning media in formal electronic modules that is integrated with a problem-based approach to learning Islamic religion. The research method is included in the type of research and development (R&D), the subjects involved in this research consisted of 2 Madrasah Tsanawiyah (MTs) teachers and students, as well as 4 experts. The data collection technique used is a non-test technique with the instrument being an expert validation questionnaire and the practicality of learning media. The data analysis technique used is descriptive with percentages to measure the level of feasibility of electronic module products. The research results showed that validation was carried out by 72% of material presentation experts, 73% of language experts, 79% of material experts, and 96% of graphics experts. The results of the practical test by teacher I was 80%, teacher II was 89% and for the practical test students in the individual test got a score of 86.9% and in the small group test it was 81.9. From these two tests, it was decided that the problem-based electronic module developed for Islamic learning at MTs was deemed suitable for use as a medium for learning activities. It is hoped that this research will be able to have a positive impact on the implementation of Fiqh learning at the junior secondary education level.